Roadmap to a sustainable city, Brighton and Hove - Barnes, J; Durrant, R; Kern, F; MacKerron, G (University of Sussex, 2016)
The roadmap has been created for the benefit of people involved in local initiatives in Brighton and Hove who are striving to create a more sustainable and low carbon future, as well as those organisations and people seeking to support and govern change within the city. Its purpose is to inform them about the context in which they are working and to help develop their future strategies. Most importantly though the creation of the roadmap was itself an important process in which many local actors participated, learned from each other and developed shared, desirable visions of the future.